Laparoscopic-assisted modified Kugel herniorrhaphy for obturator hernia: a case report. Issue 2 (7th February 2022) - Yamagishi, Shunsuke; Aramaki, Osamu; Yoshida, Nao; Mitsuka, Yusuke; Kawai, Takaharu; Yamazaki, Shintaro; Kang, Woodae; Nakayama, Hisashi; Moriguchi, Masamichi; Higaki, Tokio; Kochi, Mitsugu; Okamura, Yukiyasu
Abstract: Obturator hernia (OH) is a relatively rare disease and there are various surgical procedures for treating it. We report the case of a patient with an OH who underwent laparoscopic-assisted modified Kugel herniorrhaphy. The patient was a 74-year-old woman admitted to our hospital with nausea and abdominal distension. A diagnosis of intestinal obstruction was made because abdominal computed tomography revealed incarcerated right OH. No apparent strangulation findings were observed, and reduction was performed under ultrasound guidance. Laparoscopic-assisted modified Kugel herniorrhaphy for OH was performed. There were no signs of the bowel necrosis. Pneumoperitoneum was temporarily discontinued, and the OH was repaired by the modified Kugel herniorrhaphy. Laparoscopy confirmed that the direct Kugel patch was placed at the appropriate position. Laparoscopic-assisted modified Kugel herniorrhaphy is considered to be safe and useful for patients with OH and is considered as one of the treatment options.